Response to the growth of Soybean (Glycine max L.) Stadium Generative 1 on the application of Trichoderma sp and Pseudomonas flourescent as Biofertilizer - Abdul Wachid; Qomariana Jamila Hakim (Nabatia, 2020)
This study aims to determine the effect of Trichoderma sp and Pseudomonas biofertilizer, carried out in the village of West Tebel, Gedangan Subdistrict, Sidoarjo Regency, starting in February 2019 until March 2019. The experiment was arranged factorial using a complete randomized design followed by a 5% BNJ test repeated 4 times with the first factor is biological fertilizer Trichoderma sp. The second factor is the use of Pseudomonas biological fertilizer. The variables observed were the number of leaves, plant height, stem diameter, initial flowering time, wet weight and dry stover and roots. The results showed that the highest average observed number of leaves, plant height, stem diameter, initial flowering time, wet weight and dry stover and roots. The results of the study said that the treatment of Trichoderma sp and Pseudomonas resulted in better growth and production of soybean plants.